Relationships Between the Rulers of the Archipelago (Perspective of Traditional Javanese Historiography) - Sudirman Shomary; Roziah Roziah; Muhammad Mukhlis; Nurul Aini Sudirman (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2026)
This study examines the representation of relationships among Nusantara rulers through the lens of traditional Javanese historiography, including Nagarakertagama, Pararaton, and various Babad texts. Using a qualitative approach with a multidimensional analysis, this research explores how social, political, and religious dimensions were constructed to maintain regional stability and Javanese hegemony. The findings reveal that social relationships were built through "intimate geopolitics" via political marriages (consanguinity), which transformed political rivalry into kinship solidarity. In the political dimension, the "Cakrawala Mandala Nusantara" concept served as both a defensive strategy against external threats and a manifestation of cosmic sovereignty. Furthermore, the transition to the Islamic period shifted the paradigm of authority from caste-based structures to cosmopolitan intellectual-spiritual networks (ukhuwah). This study argues that the relationships between rulers in traditional historiography were not merely a history of conquest, but a continuous negotiation of identity aimed at building a cohesive regional order. These findings contribute to a deeper understanding of the historical roots of national integration in Indonesia.